2022
DOI: 10.15586/aei.v50i2.577
|View full text |Cite
|
Sign up to set email alerts
|

Momordica charantia L. improves airway hyperresponsiveness and suppresses inflammation in a murine model of allergic asthma

Abstract: Objective: To evaluate the effect of a hydroethanolic extract of Momordica charantia L. (“bitter melon”, Cucurbitaceae) leaves (MCHA) on ovalbumin (OVA)-induced asthma model. Balb/c mice were sensitized twice and challenged for 4 alternate days with OVA and then treated with MCHA (500 mg/kg) for 7 consecutive days. Methods: Control groups received treatment with normal saline or dexamethasone (2 mg/kg) on the same day. We assessed in vivo bronchial hyperresponsiveness and ex-vivo inflammation and mucus product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This complication not only hinders patient recovery but can also escalate postoperative complications, extend hospital stays and detrimentally affect quality of life post‐discharge. Clinical studies have indicated that sevoflurane, an alkane inhalational anaesthetic frequently utilized in general anaesthesia (GA) (Frota et al, 2022), could trigger escalated inflammation and apoptosis of hippocampal neurons in aged rats, consequently leading to cognitive dysfunction. This is considered a critical factor in POCD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This complication not only hinders patient recovery but can also escalate postoperative complications, extend hospital stays and detrimentally affect quality of life post‐discharge. Clinical studies have indicated that sevoflurane, an alkane inhalational anaesthetic frequently utilized in general anaesthesia (GA) (Frota et al, 2022), could trigger escalated inflammation and apoptosis of hippocampal neurons in aged rats, consequently leading to cognitive dysfunction. This is considered a critical factor in POCD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%